Consumption-Income Sensitivity and Portfolio Choice. (17th July 2018) - Addoum, Jawad M; Delikouras, Stefanos; Korniotis, George M
Abstract: Contrary to the predictions of traditional life-cycle models, household consumption is excessively sensitive to current income. Similarly, weak evidence of income hedging runs against standard portfolio theory. We link these two puzzles by modifying the theoretical framework of Viceira (2001) to study how consumption-income sensitivities generated by income in the utility function affect households' portfolio choices. Empirically, we find that consumption-income sensitivities affect asset allocation through the income hedging channel. In particular, we show that the interaction between consumption-income sensitivity and the correlation of income growth to stock market returns is an important explanatory variable for households' stock market holdings. Received October 20, 2016; editorial decision April 25, 2018 by Editor Wayne Ferson.